Effect of nanoclay on mechanical, thermal and morphological properties of silicone rubber and EPDM/silicone rubber hybrid composites. Issue 1 (2nd January 2021) - Rana, Ajay Singh; Vamshi, M. Kiran; Naresh, K.; Velmurugan, R.; Sarathi, R.
ABSTRACT: The effect of nanoclay on tensile properties is studied by dispersing the different weight percentages (0 wt%, 2 wt%, 4 wt% and 6 wt%) of montmorillonite (MMT) clay in the silicone rubber and hybrid rubber (EPDM/silicone rubber) samples. The thermal properties are also studied by using different instruments such as dynamic mechanical analyser (DMA), differential scanning calorimetry (DSC) and thermogravimetric analyser (TGA). The glass transition temperature (Tg ) values obtained from DMA are correlated with DSC, both the values match well. The thermal stability and change in mass of above mentioned materials as a function of temperature are measured using thermogravimetric analysis (TGA). Fourier transformed infrared spectroscopy (FTIR) is used to characterise the grafting of clay in the silicone and hybrid rubbers.